Dominant Fecal Microbiota in Newly Diagnosed Untreated Inflammatory Bowel Disease Patients. (17th November 2013) - Thorkildsen, Lill Therese; Nwosu, Felix Chinweije; Avershina, Ekaterina; Ricanek, Petr; Perminow, Gøri; Brackmann, Stephan; Vatn, Morten H.; Rudi, Knut
Abstract : Our knowledge about the microbiota associated with the onset of IBD is limited. The aim of our study was to investigate the correlation between IBD and the fecal microbiota for early diagnosed untreated patients. The fecal samples used were a part of the Inflammatory Bowel South-Eastern Norway II (IBSEN II) study and were collected from CD patients (n = 30 ), UC patients (n = 33 ), unclassified IBD (IBDU) patients (n = 3 ), and from a control group (n = 34 ). The bacteria associated with the fecal samples were analyzed using a direct 16S rRNA gene-sequencing approach combined with a multivariate curve resolution (MCR) analysis. In addition, a 16S rRNA gene clone library was prepared for the construction of bacteria-specific gene-targeted single nucleotide primer extension (SNuPE) probes. The MCR analysis resulted in the recovery of five pure components of the dominant bacteria present: Escherichia/Shigella, Faecalibacterium, Bacteroides, and two components of unclassified Clostridiales. Escherichia/Shigella was found to be significantly increased in CD patients compared to control subjects, and Faecalibacterium was found to be significantly reduced in CD patients compared to both UC patients and control subjects. Furthermore, a SNuPE probe specific for Escherichia/Shigella showed a significant overrepresentation of Escherichia/Shigella in CD patients compared to control subjects. In conclusion, samples from CD patients exhibited an increase in Escherichia/Shigella and a decrease in Faecalibacterium indicating that the onset of the disease is associated with an increase in proinflammatory and a decrease in anti-inflammatory bacteria.